Sintered Ni-Free Structural Alloy Steels – Processing, Properties and Microstructure - M. Sułowski; M. Tenerowicz-Żaba; R. Valov; V. Petkov (Archives of Metallurgy and Materials, 2020)
In this paper the development and method of production of modern, Ni-free sintered structural steels containing Cr, Mn and Mo, enabling the production of structural sintered steels in industrial conditions, using safe, with low H2-content, sintering atmospheres is presented. For this purpose, the analysis of microstructure and mechanical properties of these sintered structural steels produced in different processing conditions and also the connections between the microstructure of sintered material and its mechanical properties, was presented. Following the investigations, the appropriate chemical composition of sintered Ni-free steels with properties which are comparable or even better than those of sintered structural steels containing rich and carcinogenic nickel was choosen. Additionally, in the paper the properties of electrolitically coated carbon steels were presented, as the beginning of investigation for improving the mechanical properties of alloyed, structural sintered steels.